Prescribing competence of junior doctors: does it add up?. Issue 3 (29th November 2009) - Kidd, L; Shand, E; Beavis, R; Taylor, Z; Dunstan, F; Tuthill, D
Abstract : Background: Prescribing errors complicate a significant number of paediatric admissions. Ongoing training and monitoring of prescribing competency in junior doctors has occurred in Cardiff since 2001, alongside national measures aimed at improving training and competency. Aim: Ongoing monitoring of junior doctors' prescribing competency to assess the effect of these national and local initiatives. Methods: Junior doctors receive training and subsequent assessment on prescribing competency at induction. A 1 h bleep-free session concerning paediatric prescribing precedes completion of four prescribing tasks. British National Formulary for children and calculators are provided. Those scoring 0 or 1 are retrained before prescribing is permitted. Our previously published data of doctors between 2001 and 2004 was compared with assessment in 2007. Results: 30 junior doctors were assessed in 2007 (32 in 2001–2004). All four questions were answered correctly by 22/30, compared to 10/32 (31%) in 2001–2004. The mean score in 2007 was 93.3% compared to 57.8% previously (see table 1 ). Comparison of means with previous results demonstrated statistically significant improvement with a mean difference of 36% (95% CI 24 to 47). In 2007, eight (27%) doctors got just one question wrong and no doctor answered all questions incorrectly. In 2001–2004, 22/32 (67%) made at least one error during previous assessment, and one doctor answered all questions incorrectly. Conclusion: Ongoing monitoring of junior doctors' prescribing ability has demonstrated improvements which may be due to local and national training initiatives.